Multi-state survey of healthcare-associated infections in acute care hospitals in Brazil - Fortaleza, C. Magno Castelo Branco [UNESP] (2017)
Background Healthcare-associated infections (HCAIs) challenge public health in developing countries such as Brazil, which harbour social inequalities and variations in the complexity of healthcare and regional development. Aim To describe the prevalence of HCAIs in hospitals in a sample of hospitals in Brazil. Methods A prevalence survey conducted in 2011–13 enrolled 152 hospitals from the five macro-regions in Brazil. Hospitals were classified as large (≥200 beds), medium (50–199 beds) or small sized (<50 beds). Settings were randomly selected from a governmental database, except for 11 reference university hospitals. All patients with >48 h of admission to the study hospitals at the time of the survey were included. Trained epidemiologist nurses visited each hospital and collected data on HCAIs, subjects' demographics, and invasive procedures. Univariate and multivariate techniques were used for data analysis. Findings The overall HCAI prevalence was 10.8%. Most frequent infection sites were pneumonia (3.6%) and bloodstream infections (2.8%). Surgical site infections were found in 1.5% of the whole sample, but in 9.8% of subjects who underwent surgical procedures. The overall prevalence was greater for reference (12.6%) and large hospitals (13.5%), whereas medium- and small-sized hospitals presented rates of 7.7% and 5.5%, respectively. Only minor differences were noticed among hospitals from different macro-regions. Patients in intensive care units, using invasive devices or at extremes of age were at greater risk for HCAIs. Conclusion Prevalence rates were high in all geographic regions and hospital sizes. HCAIs must be a priority in the public health agenda of developing countries.